Reconstructing the long-term cosmic ray intensity: linear relations do not work - K. Mursula (Annales Geophysicae, 2003)
It was recently suggested (Lockwood, 2001) that the cosmic ray intensity in the neutron monitor energy range is linearly related to the coronal source flux, and can be reconstructed for the last 130 years using the long-term coronal flux estimated earlier. Moreover, Lockwood (2001) reconstructed the coronal flux for the last 500 years using a similar linear relation between the flux and the concentration of cosmogenic 10 Be isotopes in polar ice. Here we show that the applied linear relations are oversimplified and lead to unphysical results on long time scales. In particular, the cosmic ray intensity reconstructed by Lockwood (2001) for the last 130 years has a steep trend which is considerably larger than the trend estimated from observations during the last 65 years. Accordingly, the reconstructed cosmic ray intensity reaches or even exceeds the local interstellar cosmic ray flux around 1900. We argue that these unphysical results obtained when using linear relations are due to the oversimplified approach which does not take into account the complex and essentially nonlinear nature of long-term cosmic ray modulation in the heliosphere. We also compare the long-term cosmic ray intensity based on a linear treatment with the reconstruction based on a recent physical model which predicts a considerably lower cosmic ray intensity around 1900. Key words. Interplanetary physics (cosmic rays; heliopause and solar wind termination) – Geomagnetism and paleomagnetism (time variations, secular and long-term)